2017
DOI: 10.3847/1538-4357/aa92c7
|View full text |Cite|
|
Sign up to set email alerts
|

Calibrating Star Formation in WISE Using Total Infrared Luminosity

Abstract: We present accurate resolved WISE photometry of galaxies in the combined SINGS and KINGFISH sample. The luminosities in the W3 12µm and W4 23µm bands are calibrated to star formation rates (SFRs) derived using the total infrared luminosity, avoiding UV/optical uncertainties due to dust extinction corrections. The W3 relation has a 1-σ scatter of 0.15 dex over nearly 5 orders of magnitude in SFR and 12µm luminosity, and a range in host stellar mass from dwarf (10 7 M ) to ∼ 3×M (10 11.5 M ) galaxies. In the abs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
242
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(261 citation statements)
references
References 116 publications
18
242
1
Order By: Relevance
“…This remains a topic for future work. Here we suggest to bootstrap via WISE4 to take advantage of the better WISE3 data quality (in good agreement with the views of Jarrett et al 2013 ;Cluver et al 2017).…”
Section: A7 Coefficient On the Mid-ir Termsupporting
confidence: 89%
See 1 more Smart Citation
“…This remains a topic for future work. Here we suggest to bootstrap via WISE4 to take advantage of the better WISE3 data quality (in good agreement with the views of Jarrett et al 2013 ;Cluver et al 2017).…”
Section: A7 Coefficient On the Mid-ir Termsupporting
confidence: 89%
“…Although the bandpass does not match WISE perfectly, as above this provides a large sample to benchmark against. Dale et al (2017) conducted careful, by-hand aperture definition and removal of foreground stars to derived integrated photometry for the KINGFISH galaxies (see also Cluver et al 2017). Clark et al (2018) adopt a more automated approach, similar to what we do here.…”
Section: Apply Extended Source Corrections To Wisementioning
confidence: 99%
“…Previous works have suggested that some of this scatter may be due to the time-dependent nature of N/O production (i.e., a N/O "clock" ;Garnett 1990;Pilyugin 1999;Henry et al 2006). A directly observable effect of an aging ionizing stellar population is an increasing fraction of low-to high-ionization gas in the H II region (see, for example, how the shape of the ionizing continuum changes with age in Chisholm et al 2019).…”
Section: N/o Versus Metallicitymentioning
confidence: 99%
“…There are many other parameters that are measured and cataloged (e.g., nuclear concentration), but are otherwise not discussed here, details will be given in Paper II. The basic source characterization pipeline has a heritage that extends from the 2MASS Extended Source Catalogue (Jarrett et al 2000), also used in the WISE processing pipeline, and various aspects have been discussed in previous WISE work (Jarrett et al 2011(Jarrett et al , 2013Cluver et al 2014;Jarrett et al 2017;Cluver et al 2017). Below we add some additional detail relevant to large galaxies.…”
Section: Source Characterizationmentioning
confidence: 99%